Pengaruh Tren Environmental Social Governance (ESG) Terhadap Strategi Portofolio di Pasar Modal Indonesia - Rahmawatii; Soraya, Bunga; Friska Dhea Narulita; Maria Yovita R. Pandin (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the influence of Environmental Social Governance (ESG) trends on portfolio strategy in the Indonesian capital market. Using data from 11 companies listed on the Indonesia Stock Exchange and a quantitative approach through linear regression, this study found that social values have a significant effect on portfolio strategy with a p-value of 0.048, while environmental and governance values do not show a significant effect (p-value 0.068 and 0.051 respectively). In addition, the combined ESG scores did not have a significant effect on portfolio strategy with a p-value of 0.134. These findings suggest that despite the increasing attention to social factors, investors in Indonesia still tend to focus on traditional financial aspects in making investment decisions. Thus, especially in the context of the Indonesian capital market, there needs to be further promotion and education on the importance of ESG in investment.